Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Claro, vamos a realizar la verificación de que [tex]\( AB \)[/tex] es simétrica para las dos parejas de matrices [tex]\( A \)[/tex] y [tex]\( B \)[/tex].
### Parte (a)
Dadas las matrices:
[tex]\[ A = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \][/tex]
[tex]\[ B = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \][/tex]
Paso 1: Calculemos [tex]\( AB \)[/tex].
[tex]\[ AB = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} = \begin{array}{cc} (2 \cdot 3 + 0 \cdot 0) & (2 \cdot 0 + 0 \cdot -10) \\ (0 \cdot 3 + 5 \cdot 0) & (0 \cdot 0 + 5 \cdot -10) \end{array} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Paso 2: Calculemos [tex]\( B^{\top} A^{\top} \)[/tex].
Primero tomamos las transpuestas:
[tex]\[ A^{\top} = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \][/tex] (como A es simétrica, A = [tex]\( A^{\top} \)[/tex])
[tex]\[ B^{\top} = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \][/tex] (como B es simétrica, B = [tex]\( B^{\top} \)[/tex])
Luego calculamos el producto:
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} = \begin{array}{cc} (3 \cdot 2 + 0 \cdot 0) & (3 \cdot 0 + 0 \cdot 5) \\ (0 \cdot 2 + -10 \cdot 0) & (0 \cdot 0 + -10 \cdot 5) \end{array} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Paso 3: Comparación
Comparando los resultados de [tex]\( AB \)[/tex] y [tex]\( B^{\top} A^{\top} \)[/tex]:
[tex]\[ AB = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Los dos son iguales, por lo que [tex]\( AB \)[/tex] es simétrica.
### Parte (b)
Dadas las matrices:
[tex]\[ A = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \][/tex]
[tex]\[ B = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \][/tex]
Paso 1: Calculemos [tex]\( AB \)[/tex].
[tex]\[ AB = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} = \begin{array}{cc} (0 \cdot 1 + -5 \cdot 2) & (0 \cdot 2 + -5 \cdot 0) \\ (-5 \cdot 1 + 1 \cdot 2) & (-5 \cdot 2 + 1 \cdot 0) \end{array} = \begin{array}{cc} -10 & 0 \\ -3 & -10 \end{array} \][/tex]
Paso 2: Calculemos [tex]\( B^{\top} A^{\top} \)[/tex].
Primero las transpuestas:
[tex]\[ A^{\top} = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \][/tex] (como A es simétrica, A = [tex]\( A^{\top} \)[/tex])
[tex]\[ B^{\top} = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \][/tex] (como B es simétrica, B = [tex]\( B^{\top} \)[/tex])
Luego calculamos el producto:
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} = \begin{array}{cc} (1 \cdot 0 + 2 \cdot -5) & (1 \cdot -5 + 2 \cdot 1) \\ (2 \cdot 0 + 0 \cdot -5) & (2 \cdot -5 + 0 \cdot 1) \end{array} = \begin{array}{cc} -10 & -3 \\ 0 & -10 \end{array} \][/tex]
Paso 3: Comparación
Comparando los resultados de [tex]\( AB \)[/tex] y [tex]\( B^{\top} A^{\top} \)[/tex]:
[tex]\[ AB = \begin{array}{cc} -10 & 0 \\ -3 & -10 \end{array} \][/tex]
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} -10 & -3 \\ 0 & -10 \end{array} \][/tex]
Los dos no son iguales, por lo que [tex]\( AB \)[/tex] no es simétrica.
### Resumen
- En la parte (a), [tex]\( AB \)[/tex] resultó simétrica.
- En la parte (b), [tex]\( AB \)[/tex] no resultó simétrica.
### Parte (a)
Dadas las matrices:
[tex]\[ A = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \][/tex]
[tex]\[ B = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \][/tex]
Paso 1: Calculemos [tex]\( AB \)[/tex].
[tex]\[ AB = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} = \begin{array}{cc} (2 \cdot 3 + 0 \cdot 0) & (2 \cdot 0 + 0 \cdot -10) \\ (0 \cdot 3 + 5 \cdot 0) & (0 \cdot 0 + 5 \cdot -10) \end{array} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Paso 2: Calculemos [tex]\( B^{\top} A^{\top} \)[/tex].
Primero tomamos las transpuestas:
[tex]\[ A^{\top} = \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} \][/tex] (como A es simétrica, A = [tex]\( A^{\top} \)[/tex])
[tex]\[ B^{\top} = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \][/tex] (como B es simétrica, B = [tex]\( B^{\top} \)[/tex])
Luego calculamos el producto:
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 3 & 0 \\ 0 & -10 \end{array} \begin{array}{cc} 2 & 0 \\ 0 & 5 \end{array} = \begin{array}{cc} (3 \cdot 2 + 0 \cdot 0) & (3 \cdot 0 + 0 \cdot 5) \\ (0 \cdot 2 + -10 \cdot 0) & (0 \cdot 0 + -10 \cdot 5) \end{array} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Paso 3: Comparación
Comparando los resultados de [tex]\( AB \)[/tex] y [tex]\( B^{\top} A^{\top} \)[/tex]:
[tex]\[ AB = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 6 & 0 \\ 0 & -50 \end{array} \][/tex]
Los dos son iguales, por lo que [tex]\( AB \)[/tex] es simétrica.
### Parte (b)
Dadas las matrices:
[tex]\[ A = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \][/tex]
[tex]\[ B = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \][/tex]
Paso 1: Calculemos [tex]\( AB \)[/tex].
[tex]\[ AB = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} = \begin{array}{cc} (0 \cdot 1 + -5 \cdot 2) & (0 \cdot 2 + -5 \cdot 0) \\ (-5 \cdot 1 + 1 \cdot 2) & (-5 \cdot 2 + 1 \cdot 0) \end{array} = \begin{array}{cc} -10 & 0 \\ -3 & -10 \end{array} \][/tex]
Paso 2: Calculemos [tex]\( B^{\top} A^{\top} \)[/tex].
Primero las transpuestas:
[tex]\[ A^{\top} = \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} \][/tex] (como A es simétrica, A = [tex]\( A^{\top} \)[/tex])
[tex]\[ B^{\top} = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \][/tex] (como B es simétrica, B = [tex]\( B^{\top} \)[/tex])
Luego calculamos el producto:
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} 1 & 2 \\ 2 & 0 \end{array} \begin{array}{cc} 0 & -5 \\ -5 & 1 \end{array} = \begin{array}{cc} (1 \cdot 0 + 2 \cdot -5) & (1 \cdot -5 + 2 \cdot 1) \\ (2 \cdot 0 + 0 \cdot -5) & (2 \cdot -5 + 0 \cdot 1) \end{array} = \begin{array}{cc} -10 & -3 \\ 0 & -10 \end{array} \][/tex]
Paso 3: Comparación
Comparando los resultados de [tex]\( AB \)[/tex] y [tex]\( B^{\top} A^{\top} \)[/tex]:
[tex]\[ AB = \begin{array}{cc} -10 & 0 \\ -3 & -10 \end{array} \][/tex]
[tex]\[ B^{\top} A^{\top} = \begin{array}{cc} -10 & -3 \\ 0 & -10 \end{array} \][/tex]
Los dos no son iguales, por lo que [tex]\( AB \)[/tex] no es simétrica.
### Resumen
- En la parte (a), [tex]\( AB \)[/tex] resultó simétrica.
- En la parte (b), [tex]\( AB \)[/tex] no resultó simétrica.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.